P40. Delta-9-Tetrahydrocannabinol-cannabidiol (THC/CBD) oromucosal spray for the treatment of spasticity in ALS – Assessment of patient reported outcomes. Issue 8 (August 2018) - Funke, A.; Spittel, S.; Kettemann, D.; Maier, A.; Münch, C.; Meyer, T.
Abstract : Background: Treatment of spasticity poses a major challenge in ALS patient management. Antispasticity medication may be limited due to side effects or to exacerbation of muscle weakness. Delta-9-tetrahydrocannabinol (THC)/cannabidiol (CBD) oromucosal spray (Sativex®), approved for multiple sclerosis spasticity second line treatment, might be an off-label treatment option in ALS patients with resistant spasticity. Although THC/CBD is known to be used in a subgroup of ALS patients few systematic investigations have been reported. Methods: A retrospective observational study investigated patients with ALS, spasticity and prescribed THC/CBD treatment, who were registered on the internet platform Ambulanzpartner Versorgungsportal (www.ambulanzpartner.de). The survey addressed the region and severity of spasticity (numeric rating scale), dosage of THC/CBD, treatment satisfaction as assessed by the Net Promoter Score (NPS) and the 9-item treatment satisfaction questionnaire for medication (TSQM9). Results: 68 patients with ALS, spasticity and prescribed THC/CBD were identified. 44 patients responded to the survey (64%). The median age of participants was 58 years (27–87 years). Most commonly, spasticity was located in the lower limbs (95%; n = 42). THC/CBD was used in male and female patients alike (ratio 43%/57%). Most patients (78%; n = 25) reported at least one application per day (daily use), whereas 22% of patients used it less often (13% weekly, 9% monthly). There was a wide range in the dosage of THC/CBD in ALS (Fig. 1 ). The median dosage was 6 oromucosal spray applications per day (2.7 mg THC/ 2.5 mg CBD each). 25% of patients report 1–2 applications per day (infrequent use) whereas another 25% of patients report more than 10 applications per day (frequent use). The NPS assessment revealed a good satisfaction of ALS patients with THC/CBD (NPS sum score: +4.9). Analysis of TSQM9 demonstrated high treatment satisfaction for several TSQM9 subdomains including 'effectiveness' (70, 5), 'convenience' (76.6) and 'overall satisfaction' (75.0). Discussion: THC/CBD was used in a wide range of ALS patients regarding age and clinical presentation. The mean dosage of THC/CBD in ALS with resistant spasticity was well comparable with the dosage in the approved MS spasticity indication. The wide dosage distribution underlines that THC/CBD dosage was adjusted to the individual needs of symptom control. Patient reported outcome scores demonstrated high treatment satisfaction. However, prospective studies on THC/CBD in ALS-related spasticity and comparative investigations to other oral antispasticity medications are of interest to address the effectiveness of THC/CBD in the domains of spasticity, pain, muscle cramps, and other ALS-related symptoms. Acknowledgement: This work was supported by a grant ofAlmirall Hermal GmbH to Ambulanzpartner Soziotechnologie GmbH.